Screening for non-communicable diseases and counselling for risk factors modification in health & wellbeing clinic at a tertiary care hospital - Udgiri, Rekha; Pattankar, Tanuja; Math, Murugesh (Indian Journal of Community Health, 2024)
Non-communicable diseases like diabetes and hypertension are highly prevalent and make a substantive contribution to the global burden of morbidity and mortality in both developing and developed countries. Because lifestyle behaviors have been shown to be effective in preventing and treating several types of diseases that can ultimately lead to a high prevalence of morbidity and mortality, several widely accepted treatment guidelines for specific diseases include lifestyle modification strategies. We aim to identify the suspected cases of Diabetes Mellitus and Hypertension & the risk factors among screened participants. We found 18% of them were found to be suspected as diabetics and 5% of them were suspected to be hypertension. We observed statistically significant association with risk factors between both the known cases and suspected cases of diabetes mellitus and hypertension. Screening programs can strengthen healthcare system initiatives and reduce the growing burden of both diabetes and hypertension in India.